The mosquito fauna of the Republic of Cyprus: a revised list - Violaris, Marios; Vasquez Christodoulou, Marlen; Samanidou, Anna; Wirth, Margaret C; Hadjivassilis, Andreas (My University, 2009)
The Cyprus Public Health Service has regularly conducted mosquito surveillance in the Republic of Cyprus over the past 10 years. Twenty-three species belonging to 6 genera and 10 subgenera have been recorded to date, including species documented from earlier surveys. As a result of this program, new mosquito species for Cyprus have been recorded, including Anopheles marteri, Culex theileri, Cx. impudicus, Culiseta subochrea, and Uranotaenia unguiculata. Importantly, mosquito species previously considered eradicated have reemerged (An. sacharovi). Monitoring and identification of mosquito species is an important component of the Public Heath Service's commitment to protecting the health of residents and preventing the spread of vector-borne diseases.
Keywords: Anophelines; Culicines; Cyprus; Mosquito species; Vectors